GLUT4 in Mouse Endometrial Epithelium: Roles in Embryonic Development and Implantation - Long, Yun; Wang, Yi-cheng; Yuan, Dong-zhi; Dai, Xin-hua; Liao, Lin-chuan; Zhang, Xue-qin; Zhang, Li-xue; Ma, Yong-dan; Lei, Yi; Cui, Zhi-hui; Zhang, Jin-hu; Nie, Li; et al. (Frontiers in Physiology, 2021)
GLUT4 involves in rapid glucose uptake among various kinds of cells to contribute to glucose homeostasis. Prior data have reported that aberrant glucose metabolism by GLUT4 dysfunction in uterus could be responsible for infertility and the increased miscarriage. However, the expression and precise functions of GLUT4 in the endometrium under physiological conditions remain unknown or controversial. In this study, we observed that GLUT4 exhibits a spatiotemporal expression manner in mouse uterus on pregnant days 1-4, especially its expression increased on pregnant day4 during the window of implantation. We also determined that estrogen in conjunction with progesterone promote the expression of GLUT4 in the endometrial epithelium in vivo or in vitro. GLUT4 is an important transporter that mediates glucose transport in endometrial epithelial cells (EECs) in vitro or in vivo. In vitro, glucose uptake decreased in mouse EECs when the cells were treated with GLUT4-siRNA. In vivo, the injection of GLUT4-siRNA into one side of mouse uterine horns resulted in increased glucose concentration in uterine fluid on pregnant day4 although it was still lower than blood and impaired endometrial receptivity by inhibiting pinopodes formation and the expressions of LIF and integrin ανβ3, finally affected embryonic development and implantation. Overall, obtained results indicate that GLUT4 in the endometrial epithelium affects embryo development by altering glucose concentration in uterine fluid, it can also affect implantation by impairing endometrial receptivity due to dysfunction of GLUT4.